2022
DOI: 10.1007/s00420-022-01860-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between household cleaning product profiles evaluated by the Ménag’Score® index and asthma symptoms among women from the SEPAGES cohort

Abstract: Objective Considering household disinfectants and cleaning products (HDCP) as mixture of ingredients, rather than each ingredient individually, might help in characterizing their role in asthma. We investigated the association between HDCP and asthma, using the recently developed Ménag'Score®, a health risk assessment score based on exhaustive ingredient lists of HDCP. MethodsThe study is based on 103 female volunteers of the SEPAGES cohort (2014-2019), with repeated data (up to 3 collection times, 200 observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A recent study suggested that the household use of DCP labelled as 'green' might induce fewer risks for current asthma, compared to the use of conventional products [74]. Moreover, an association was observed between weekly household use of DCP classified with a poor Ménag'score ® (D and E), a health risk assessment score allowing to inform the consumers by a simple labelling on toxicity of cleaning products ingredients (https://www.60millions-mag.com/ 2019/08/27/produits-menagers-nocifs-les-premiers-pas-du-menag-score-16406; accessed on 16 May 2023), and more frequent asthma symptoms among 100 women [48]. The use of such a score, with a simple and intuitive labelling, might allow to improve public health prevention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study suggested that the household use of DCP labelled as 'green' might induce fewer risks for current asthma, compared to the use of conventional products [74]. Moreover, an association was observed between weekly household use of DCP classified with a poor Ménag'score ® (D and E), a health risk assessment score allowing to inform the consumers by a simple labelling on toxicity of cleaning products ingredients (https://www.60millions-mag.com/ 2019/08/27/produits-menagers-nocifs-les-premiers-pas-du-menag-score-16406; accessed on 16 May 2023), and more frequent asthma symptoms among 100 women [48]. The use of such a score, with a simple and intuitive labelling, might allow to improve public health prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional studies are needed to confirm these recent findings. Moreover, studying DCP as mixtures of complex substances rather than each substance individually is helpful for a better understanding of the health impact of DCP [48]. Data from the CRESPI cohort will allow to further study these recent research topics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers should at least be informed if they can potentially come into contact with irritant substances. Exhaustive ingredient lists of household DCPs, which are available on manufacturers' websites, may be a key tool to improve prevention [45]. Nevertheless, Lee et al [46] found that safety data sheets for DCPs used in healthcare organizations across England and Wales contained insufficient respiratory hazard information.…”
Section: Prevention Of Irritant-induced Asthmamentioning
confidence: 99%
“…Several studies have highlighted the negative impact of the use of cleaning products on asthma among adults, both at the workplace5–10 and at home,11–19 especially among women who appear to be more exposed to these products than men 3. Regarding the associations between domestic exposure to cleaning products and asthma among adults, nine studies have been published so far, of which only two had a longitudinal design 18 19.…”
Section: Introductionmentioning
confidence: 99%